GDP dynamics and unemployment changes in developed and developing countries. Issue 31 (3rd July 2018) - Bartolucci, Francesco; Choudhry, Misbah T.; Marelli, Enrico; Signorelli, Marcello
ABSTRACT: We design a new specification of Okun's model that takes the following features into account: estimation of the relation in first differences, the possible lagged effect of GDP dynamics on unemployment changes, the persistence of unemployment rate dynamics, the possible different values of Okun coefficients under recession (with respect to periods of increases in GDP), the existence of cross-country institutional and structural differences (i.e. country-specific Okun coefficients), the additional effect on unemployment caused by large adverse shocks such as financial crises. A distinctive feature of this article is its consideration of a large set of countries for which we find differentiated Okun coefficients. Moreover, we focus in particular on the distinction between developed and developing countries, and on the additional impact of financial crises. From an econometric point of view, the model developed belongs in the family of linear mixed-effects models. The estimation method uses an expectation-maximization (EM) algorithm. Our results confirm the general validity of 'Okun's law'; they show the Okun coefficient differences between high- and low-income countries; and they evidence an additional impact of some types of financial crisis on the unemployment dynamics of developed economies.